John Martin apocalypse - Myrone, Martin (Tate, 2011)
John Martin (1789-1854) is one of the most extraordinary figures in British art. His large-scale, dramatic paintings, encompassing catastrophe, war, apocalypse and nature on an epic scale, were the disaster movies of their day. This title presents a comprehensive reassessment of his career